Social differentiation of the peasantry (Marxist). Issue 7 (10th November 2022) - Cousins, Ben
ABSTRACT: Marxist understandings of the peasantry focus largely on class relations and seek to locate rural households within wider sets of class structures and dynamics. This article reviews debates and controversies amongst Marxists on the classic agrarian question, class differentiation within processes of transition from pre-capitalist to fully capitalist societies, land reform and class relations, whether or not to characterize peasants as petty commodity producers, the relationship between class and other forms of social differentiation such as gender, race, ethnicity and caste, and the role of class differentiation in peasant politics.